Insights into the roles of exogenous phenylalanine and tyrosine in improving rapamycin production of Streptomyces rapamycinicus with transcriptome analysis - Dongmei Xu; Yaoyao Wang; Hongzhen Li; Bing Wang; Libin Chai; Li Feng; Fengzhi Ren; Xuejin Zhao; Xuexia Zhang (Microbial Cell Factories)
Abstract Rapamycin is an important natural macrolide antibiotic with antifungal, immunosuppressive and antitumor activities produced by Streptomyces rapamycinicus. However, their prospective applications are limited by low fermentation units. In this study, we found that the exogenous aromatic amino acids phenylalanine and tyrosine could effectively increase the yield of rapamycin in industrial microbial fermentation. To gain insight into the mechanism of rapamycin overproduction, comparative transcriptomic profiling was performed between media with and without phenylalanine and tyrosine addition. The results showed that the addition of phenylalanine and tyrosine upregulated the transcription levels of genes involved in rapamycin biosynthesis, precursor production, and transporters. In addition, the transcription levels of many carbohydrate metabolism-related genes were down-regulated, leading to a decrease in growth, suggesting that balancing cell growth and rapamycin biosynthesis may be important to promote efficient biosynthesis of rapamycin in Streptomyces rapamycinicus. These results provide a basis for understanding physiological roles of phenylalanine and tyrosine, and a new way to increase rapamycin production in Streptomyces cultures.